2003
DOI: 10.1046/j.1440-169x.2003.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological regulation of P‐glycoprotein, MRP1, MRP2 and cytochrome P450 3A2 during rat ontogeny

Abstract: P-glycoprotein and the multidrug resistance-related proteins MRP1 and MRP2 belong to the ATP binding cassette family of proteins and transport a wide range of substrates. These proteins are also involved in metabolic and excretory processes of xenobiotics. The rat genes mdr1a and mdr1b code for P-glycoproteins, while mrp1 and mrp2 genes code for MRP1 and MRP2 proteins, respectively. In this study, the physiological modulation of the level of transcript for these genes during rat ontogeny in the liver, kidney, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
50
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 35 publications
13
50
0
Order By: Relevance
“…The group detected abruptly high levels of mdr1b at 21 d (21), but no formal statistical analysis was presented. Rosati et al also demonstrated regulation of P-gp postnatally (22). They found that levels of both mdr1a and mdr1b at birth had significant increases from postnatal Day 6 onwards in the kidney, which corresponds to our Day 7.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The group detected abruptly high levels of mdr1b at 21 d (21), but no formal statistical analysis was presented. Rosati et al also demonstrated regulation of P-gp postnatally (22). They found that levels of both mdr1a and mdr1b at birth had significant increases from postnatal Day 6 onwards in the kidney, which corresponds to our Day 7.…”
Section: Discussionmentioning
confidence: 84%
“…Dutt (13,21,22). We used FVB mice in our study, similar to Mahmood et al The use of different techniques could also account for some differences seen.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expression levels of Mdr1a, Mdr1b and Mrp2 transcripts are relatively low in fetal and neonatal rats but, after birth, increase dramatically, and reach adult levels at 3 to 5 weeks old. However, the expression level of Mrp1 transcript does not show any modulation (Rosati et al, 2003).…”
Section: Functionmentioning
confidence: 89%
“…Only one report did not detect MRP in human heart (Sugawara et al, 1997). MRP1 mRNA was found to be abundant in the heart of CD1 mice and chickens by Northern blot analysis, and in rats by RT-PCR (Stride et al, 1996;Hagen et al, 2000;Rosati et al, 2003). Moreover, Ghosh et al (2004) observed cardiac MRP1 gene expression by PCR in heart of Wistar rats, which was increased in diabetic cardiomyocytes.…”
Section: Abc Transporters and Distribution Of Drugs To The Heartmentioning
confidence: 99%
“…Further work is required to elucidate the precise biological functions of ABCD2 and ABCA transporters. Rosati et al, (2003) studied the physiological modulation of mdr1a, mdr1b, mrp1 and mrp2 in some tissues including the heart during rat ontogeny. In this research in which hearts were collected at different developmental stages, both mdr1a and mdr1b levels of transcript were detected by RT-PCR and increased during rat ontogeny to obtain the highest levels at 30 and/or 60 days of age.…”
Section: Abc Transporters and Distribution Of Drugs To The Heartmentioning
confidence: 99%